The role of RNA processing in the pathogenesis of motor neuron degeneration. - Bäumer, D; Ansorge, O; Almeida, M; Talbot, K (2010)
Motor neurons are large, highly polarised cells with very long axons and a requirement for precise spatial and temporal gene expression. Neurodegenerative disorders characterised by selective motor neuron vulnerability include various forms of amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA). A rapid expansion in knowledge on the pathophysiology of motor neuron degeneration has occurred in recent years, largely through the identification of genes leading to familial forms of ALS and SMA. The major emerging theme is that motor neuron degeneration can result from mutation in genes that encode factors important for ribonucleoprotein biogenesis and RNA processing, including splicing regulation, transcript stabilisation, translational repression and localisation of mRNA. Complete understanding of how these pathways interact and elucidation of specialised mechanisms for mRNA targeting and processing in motor neurons are likely to produce new targets for therapy in ALS and related disorders.